Quality of Work Life among Professional Nurses in Nakhonpathom Hospital - Promeiang, Praparat; Suwannapong, Nawarat; Thipayamongkolkul, Mathuros; Boonshuya, Chaweewan (Journal of Health Science of Thailand, 2017)
Professional nurses are the majority of the manpower in any health facility. Nursing is a highly responsible occupation and encounters many risk factors all of which may affect the quality of work life. This research is a cross-sectional study with the objectives to assess the quality of work life, the perceptions of the organizational climate and the work values of professional nurses working in Nakhon Pathom hospital; and to find the relationship between personal characteristics which include gender, age, marital status, educational level, professional level, duration of work, and income, the perceptions of organizational climate, work values and the quality of their work life. Data were collected through 445 copies of a questionnaire sent to registered nurses working in the hospital. The survey was conducted during April - June 2557, and analyzed by simple linear regression and stepwise multiple regression. The rate of survey response was 61.3 percent. The results showed that the majority of registered nurses (70.0%) were at a moderate level in the quality of work life, the perceptions of organizational climate and the values were overall at a moderate level (77.3% and 69.2%, respectively). Registered nurses’ perceptions of organizational climate and values had a positively statistical significance correlated to the quality of work life (p <0.05). There were five factors used to predict the registered nurses’ quality of work life, which were social conditions, task relevance and engagement, science and technology utilized in the department, participation in decision-making, and the prospect of promotion, and the result was 28.4 percent (R2 adj.= 0.284). As a consequence, Nakhon Pathom hospital should encourage registered nurses to treat their patients with a service mind, regularly provide innovation and medical science technology training, and to support adequate welfare in promoting career advancement, in order to improve and maintain the standard of the quality of the work life in the organization.